First report on status and prospects of Loranthus in mango orchards: A potential threat to mango based agroforestry system - Yadav, Ashok; Dhakar, Manish Kumar; Kumar, Sushil; Handa, A.K.; Arunachalam, A. (Indian Journal of Agroforestry, 2021)
The present study on Loranthus infestation and intensity analysis indicates that it has become a serious issue for mango growers. All the varieties are prone to attack by Loranthus/Mistletoes. However, the large sized tree canopies (i.e. Fazli) are highly infested whereas small tree canopy are less infested. The result on farmers’ responses revealed that it affects several aspects i.e. problem in harvesting, blocks light penetration inside the canopy, affects quality of the mango, nutrient absorption, water absorption, and growth and development of the mango tree. Study recorded a total of four Loranthus species, namely Dendrophthoe falcata (L.f.) Ettingsh., Loranthus worcesteri Mer., Loranthus gardneri Thwaites and Loranthus longiflorus Desr. on mango tree in Malda district of West Bengal.